2020
DOI: 10.1038/s41396-020-0606-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and evolutionary history of a mycorrhizal fungus regulate the currency of exchange in symbiosis with the food security crop cassava

Abstract: Most land plants form symbioses with arbuscular mycorrhizal fungi (AMF). Diversity of AMF increases plant community productivity and plant diversity. For decades, it was known that plants trade carbohydrates for phosphate with their fungal symbionts. However, recent studies show that plant-derived lipids probably represent the most essential currency of exchange. Understanding the regulation of plant genes involved in the currency of exchange is crucial to understanding stability of this mutualism. Plants enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Quantitative genetic variation among SSSLs is likely significant for their symbiotic interaction with plants, since SSSLs differ significantly in fungal quantitative traits, how they colonize roots, and how they affect plant biomass (Ehinger et al, 2012;Angelard et al, 2014;Savary et al, 2018a). Indeed, pot experiments with rice, as well as field studies with cassava, indicate that genetic variation among SSSLs has enormous effects on plant biomass (Angelard et al, 2010;Ceballos et al, 2013Ceballos et al, , 2019Mateus et al, 2019;Savary et al, 2020). The link between qualitative genetic variation (presence or absence of single-nucleotide polymorphisms (SNPs)) of R. irregularis isolates and plant growth was recently presented by Ceballos et al (2019), although likely depends additionally on plant host, edaphic characteristics, and other biotic and abiotic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative genetic variation among SSSLs is likely significant for their symbiotic interaction with plants, since SSSLs differ significantly in fungal quantitative traits, how they colonize roots, and how they affect plant biomass (Ehinger et al, 2012;Angelard et al, 2014;Savary et al, 2018a). Indeed, pot experiments with rice, as well as field studies with cassava, indicate that genetic variation among SSSLs has enormous effects on plant biomass (Angelard et al, 2010;Ceballos et al, 2013Ceballos et al, , 2019Mateus et al, 2019;Savary et al, 2020). The link between qualitative genetic variation (presence or absence of single-nucleotide polymorphisms (SNPs)) of R. irregularis isolates and plant growth was recently presented by Ceballos et al (2019), although likely depends additionally on plant host, edaphic characteristics, and other biotic and abiotic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In another study considering nutrient trading (Hortal et al ., 2017), the P. microcarpus isolates R10 and Si9 exhibited opposing nutrient trading strategies, with R10 donating very little nitrogen to the plant while consuming more carbon and Si9 donating more nitrogen for less carbon. Experiments with arbuscular mycorrhizal fungi have demonstrated that different isolates within a species have significant effects on the resulting biomass, nutritional status and metabolism of the host plant (Koch et al ., 2006; Mensah et al ., 2015; Savary et al ., 2020). This isolate‐specific effect on plant host performance may be tied to large differences discovered in the genomes of AM fungi within a species (Chen et al ., 2018; Savary et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with arbuscular mycorrhizal fungi have demonstrated that different isolates within a species have significant effects on the resulting biomass, nutritional status and metabolism of the host plant (Koch et al ., 2006; Mensah et al ., 2015; Savary et al ., 2020). This isolate‐specific effect on plant host performance may be tied to large differences discovered in the genomes of AM fungi within a species (Chen et al ., 2018; Savary et al ., 2020). Within ECM fungi, intra‐species genome divergence has also been shown, as, for example, in populations of Suillus brevipes (Branco et al ., 2015), though the extent of genome variation within Pisolithus species studied here is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we showed that CaMg living in R. irregularis do not harbor high within host diversity compare to other CaMg based on their 16S sequences and have reduced genome size and gene content. Results from previous studies on R. irregularis isolate A2 have shown a strong decrease in sporulation rate (Koch et al, 2004) and low colonization rate (Savary et al, 2020) in this R. irregularis isolate compared to other non-CaMg harbouring isolates of the same species and population. These results suggest that the presence of the endobacteria within this isolate could potentially come at a fitness cost to the A2 fungus and supports the hypothesis of a parasitic nature of the CaMg (Toomer et al, 2015).…”
Section: The Potential Role Of Ricamg Bacteria In R Irregularismentioning
confidence: 49%
“…A high variation in AMF phenotypic traits and plant responses have been widely observed, even when using AMF isolates of the same species (Koch et al, 2006, Klironomos et al, 2003. This variation could be the result of different AMF genetic background (Savary et al, 2018, Savary et al, 2020. However, the role of the presence/absence of a potential endoparasitic bacteria in AMF used for plant-AMF experiment has never been studied and could be an interesting and potential source of variation in the outcome of the symbiosis.…”
Section: A Role In Of the Tripartite Symbiosis?mentioning
confidence: 99%